Biological control of red rot disease of sugarcane through Trichoderma harzianum and Trichoderma viride - and B.B. JOSHI, VIJAI SINGH*, S.N. SRIVASTAVA, RAM JI LAL, S.K. AWASTHI (Indian Phytopathology, 2008)
Several soil samples (76) from sugarcane rhizosphere were collected from U.P. and Bihar and strains of Trichoderma harzianum and T. viride were isolated on Trichoderma specific medium. The antagonistic activity of these isolates was tested against red rot pathogen (Colletotrichum falcatum Went.). T. harzianum strains were found to be more efficient than T. viride in dual culture as well as in field testing. Red rot control was evaluated in highly susceptible variety (CoLk 7701). Healthy plant - cane crop was grown with sett and soil treatments by T. harzianum and T. viride. The developed canes were inoculated with the virulent pathotype Cf 09 identified from CoS 767. T. harzianum strain T 37 was found to be highly effective. Red rot was completely controlled in 47–48% canes by T 37. In remaining 52–53% canes the disease symptom severity was reduced to 4–6 grade on 0–9 scale. T. viride strain T 6 was able to completely control the disease in 24–28% canes and provide partial control in 72–76% canes. But severe symptoms of red rot were produced in 97–100% canes in case of untreated check. The population of both the species of Trichoderma was invariably present in all the sugarcane rhizosphere soil but every strain isolated was not efficient. The biocontrol of red rot offered by T harzianum and T. viride up to 5-6 months may be due to direct parasitic action of Trichoderma and also may be induced systemic resistance in sugarcane by the enzymatic actions of the metabolites released by the bioagent. The effect may be utilised for cultivating the susceptible and moderately resistant varieties for some more years. In addition to red rot control T. harzianum and T. viride were also improved the germination, number of tillers, number of millable canes and yield. An increase in plant cane productivity of 4.4 and 10.0 t / ha by sett and soil treatment with T. harzianum was recorded. T. viride was able to enhance the yield by 3.6 and 9.0 t / ha through sett and soil application.